Augmented H2S production via cystathionine-beta-synthase upregulation plays a role in pregnancy-associated uterine vasodilation†. Issue 3 (24th January 2017) - Sheibani, Lili; Lechuga, Thomas J.; Zhang, Honghai; Hameed, Afshan; Wing, Deborah A.; Kumar, Sathish; Rosenfeld, Charles R.; Chen, Dong-bao
Abstract: Endogenous hydrogen sulfide (H2 S) synthesized via metabolizing L-cysteine by cystathionine-beta-synthase (CBS) and cystathionine-gamma-lyase (CSE) is a potent vasodilator and angiogenic factor. The objectives of this study were to determine if human uterine artery (UA) H2 S production increases with augmented expression and/or activity of CBS and/or CSE during the menstrual cycle and pregnancy and whether exogenous H2 S dilates UA. Uterine arteries from nonpregnant (NP) premenopausal proliferative (pPRM) and secretory (sPRM) phases of the menstrual cycle and pregnant (P) women were studied. H2 S production was measured by the methylene blue assay. CBS and CSE mRNAs were assessed by quantitative real-time PCR, and proteins were assessed by immunoblotting and semiquantitative immunofluorescence microscopy. Effects of H2 S on rat UA relaxation were determined by wire myography ex vivo . H2 S production was greater in NP pPRM and P than NP sPRM UAs and inhibited by the specific CBS but not CSE inhibitor. CBS but not CSE mRNA and protein were greater in NP pPRM and P than NP sPRM UAs. CBS protein was localized to endothelium and smooth muscle and its levels were in a quantitative order of P >NP UAs of pPRM>sPRM. CSE protein was localized in UA endothelium and smooth muscle with no difference among groups. A H2 S donor relaxed P > NP UAs but not mesentery artery. Thus, human UA H2 S production is augmented with endothelium and smooth muscle CBS upregulation, contributing to UA vasodilation in the estrogen-dominant physiological states in the proliferative phase of the menstrual cycle and pregnancy. Summary Sentence: Augmented hydrogen sulfide biosynthesis via upregulating endothelium and smooth muscle cystathionine β-synthase expression plays a role in pregnancy-associated uterine vasodilation.